2008
DOI: 10.1074/jbc.m709897200
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl Oxidase Oxidizes Cell Membrane Proteins and Enhances the Chemotactic Response of Vascular Smooth Muscle Cells

Abstract: Lysyl oxidase (LOX)3 catalyzes the oxidation of specific lysine residues within extracellular elastin and collagen thus generating residues of ␣-aminoadipic-␦-semialdehyde within these proteins (1). These peptidyl aldehydes can then undergo condensation with vicinal ␣-aminoadipic-␦-semialdehyde or unmodified lysine residues to form inter-and intrapeptide covalent cross-linkages that stabilize these fibrous proteins. In addition to the non-ionic aldehyde product, the LOX-catalyzed reaction acting on protonated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 53 publications
8
89
0
Order By: Relevance
“…Supporting a positive role for ROS on SHP2 activation, evidence shows that oxidative stress induces tyrosine phosphorylation of SHP2 at the C terminus through a mechanism involving the formation of lipid rafts and caveolin1 expression (39,40). Similar results have been demonstrated in response to exogenous hydrogen peroxide treatment (55) and the inhibition of lysyl oxidase (56).…”
Section: Discussionsupporting
confidence: 71%
“…Supporting a positive role for ROS on SHP2 activation, evidence shows that oxidative stress induces tyrosine phosphorylation of SHP2 at the C terminus through a mechanism involving the formation of lipid rafts and caveolin1 expression (39,40). Similar results have been demonstrated in response to exogenous hydrogen peroxide treatment (55) and the inhibition of lysyl oxidase (56).…”
Section: Discussionsupporting
confidence: 71%
“…LOXmediated migration is correlated with Src and FAK phosphorylation because of hydrogen peroxyde generation 38 or of oxidation of cell surface receptors. 40 Multiple levels of cell-ECM interactions are potentially involved in capillary formation. Here, we demonstrate that col4a1 …”
Section: Discussionmentioning
confidence: 99%
“…In parallel studies, highly purified human sVAP-1 induced dose-dependent migration of peripheral blood lymphocytes in Boyden chamber assays with a maximal response between 10 and 100 ng/ml ( Figure 3G) that was comparable to that seen with 10 ng/ml CXCL12, a potent lymphocyte chemotactic factor. The related amine oxidase LOX has been shown to promote the migration of smooth muscle cells and monocytes through the action of H 2 O 2 (33,34), and a recent study in zebrafish reported that H 2 O 2 produced by an unspecified amine oxidase promotes leukocyte recruitment during wound healing (35). This led us to investigate whether the promigratory effects VAP-1 deficiency attenuates leukocyte infiltration into the liver during fibrogenesis.…”
Section: Circulating Serum [Svap-1] Is Significantly Elevated In Humamentioning
confidence: 99%